GURU POFESIONAL DALAM PANDANGAN ISLAM - Misnan, Misnan; Hanafiah, Muhibuddin; Hadi, Abdul (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2026)
Teachers are at the forefront of successful curriculum implementation and the achievement of educational goals. This study aims to analyze the importance of teacher professionalism in managing competency-based learning processes. The primary focus of the study lies in how teachers’ abilities to facilitate effective learning, foster student motivation, and integrate relevant learning media. The method used in this study is a qualitative approach with descriptive-analytical analysis. The results indicate that the perfection of a curriculum holds no meaning without being supported by competent teachers. Teacher professionalism is not merely grounded in subject matter mastery but also in a calling, moral responsibility, commitment, and creativity. Educators who are aware of their role will demonstrate consistency in behavior and personality and possess a spirit of continuous learning (learning how to learn). In conclusion, the success of education depends heavily on the quality of educators who are capable of serving as role models and dynamic facilitators of learning. Awareness of professional responsibility drives teachers to continually enhance their capabilities to realize the ideal goals of education.